PERANAN KESEJAHTERAAN DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. BANK RAKYAT INDONESIA TBK CABANG PONDOK GEDE - Kemal Taufik; Adrian Dhika (Sekolah Tinggi Manajemen IMMI Jakarta, 2020)
The important employee welfare defend employee so that doesn't move to company other, freshment gift manner to officials with appropriate work environment situation and resort condition. supposed good work environment can spur on tall official performance. This problem formulation : 1) What found welfare part towards employee performance in PT. Bank Rakyat Indonesia Tbk Cabang Pondok Gede?; 2) What found work environment part towards employee performance in PT. Bank Rakyat Indonesia Tbk Cabang Pondok Gede?; 3) What found welfare part and work environment according to together towards employee performance in PT. Bank Rakyat Indonesia Tbk Cabang Pondok Gede? This watchfulness aim : 1) To detect welfare part magnitude towards employee performance in PT. Bank Rakyat Indonesia Tbk Cabang Pondok Gede. 2) To detect work environment part magnitude towards employee performance in PT. Bank Rakyat Indonesia Tbk Cabang Pondok Gede. 3) To detect welfare part magnitude and work environment according to together towards employee performance in PT. Bank Rakyat Indonesia Tbk Cabang Pondok Gede. Conclusion : 1) Found connection significant welfare towards employee performance in PT. Bank Rakyat Indonesia Tbk Cabang Pondok Gede, with indicator-indicator well-being guarantee, work arrangement, placidity guarantee, organization progress, creat work environment, complete work facilities, well-being facilities, official library, official education, official house, matter need, official hope, pension, official work quality and economy security. 2) Found connection significant work environment towards employee performance in PT. Bank Rakyat Indonesia Tbk Cabang Pondok Gede, with indicator-indicator work smoothness, light, temperature at work, draught, cool taste, planology, temperature, voice, illumination, noise, illumination enough, illumination less, air transfer enough, air transfer can refresh physical and calm work environment. 3) Found positive connection and significant welfare and environment work according to together towards employee performance in PT. Bank Rakyat Indonesia Tbk Cabang Pondok Gede, with indicator-indicator education, practice, nutrient and well-being, income, self development, management, government wisdom, official fellow connection, connection with pmpinan, supervision connection, supervise, official know-how, working procedure, increase connection and incentive system.